The effect of type of vaginal insert and dose of pLH on embryo production, following fixed-time AI in a progestin-based superstimulatory protocol in Nelore cattle - Nogueira, Marcelo F. Gouveia [UNESP]; Fragnito, Paulo S.; Trinca, Luzia A. [UNESP]; Barros, Ciro M. [UNESP] (Elsevier, 2007)
The objective was to analyze and report field data focusing on the effect of type of progesterone-releasing vaginal insert and dose of pLH on embryo production, following a superstimulatory protocol involving fixed-time artificial insemination (FTAI) in Nelore cattle (Bos taurus indicus). Donor heifers and cows (n = 68; 136 superstimulations over 2 years) received an intravaginal, progesterone-releasing insert (CIDR® or DIB®, with 1.9 or 1.0 g progesterone, respectively) and 3-4 mg of estradiol benzoate (EB) i.m. at random stages of the estrous cycle. Five days later (designated Day 0), cattle were superstimulated with a total of 120-200 mg of pFSH (Folltropin-V®), given twice daily in decreasing doses from Days 0 to 3. All cattle received two luteolytic doses of PGF2α at 08:00 and 20:00 h on Day 2 and progesterone inserts were removed at 20:00 h on Day 3 (36 h after the first PGF2α injection). Ovulation was induced with pLH (Lutropin-V®, 12.5 or 25 mg, i.m.) at 08:00 h on Day 4 with FTAI 12, 24 and in several cases, 36 h later. Embryos were recovered on Days 11 or 12, graded and transferred to synchronous recipients. Overall, the mean (±S.E.M.) number of total ova/embryos (13.3 ± 0.8) and viable embryos (9.4 ± 0.6) and pregnancy rate (43.5%; 528/1213) did not differ among groups, but embryo viability rate (overall, 70.8%) was higher in donors with a DIB (72.3%) than a CIDR (68.3%, P = 0.007). In conclusion, the administration of pLH 12 h after progesterone removal in a progestin-based superstimulatory protocol facilitated fixed-time AI in Nelore donors, with embryo production, embryo viability and pregnancy rates after embryo transfer, comparable to published results where estrus detection and AI was done. Results suggested a possible alternative, which would eliminate the need for estrus detection in donors. © 2006 Elsevier Inc. All rights reserved.
Keywords: Bovine; Embryo transfer; pLH; Progesterone; Superovulation; gestagen; hormone; luteinizing hormone; animal; animal disease; artificial insemination; cattle; clinical trial; drug effect; embryo (anatomy); female; intravaginal drug administration; methodology; ovulation induction; physiology; pregnancy; pregnancy rate; reproduction; Administration, Intravaginal; Animals; Cattle; Embryo, Mammalian; Female; Hormones; Insemination, Artificial; Luteinizing Hormone; Ovulation Induction; Pregnancy; Pregnancy Rate; Progestins; Reproduction; Bos indicus; Bos taurus